An analysis of financial speculation: from the Maqasid Al-Shari'ah perspective. Issue 1 (13th February 2017) - Rafikov, Ildus; Saiti, Buerhan
Abstract : Purpose: This paper aims to discuss the topic of financial speculation with special reference to forex and offers an analysis from the Maqasid Al-Shari ' ah perspective, whereby authors propose to limit the outreach of speculative instruments in the financial markets. Design/methodology/approach: The authors will make use of a simple textual analysis of existing materials and documents. To come up with conclusions, relevant to this study and to make them credible enough, the authors will undertake to review the existing literature in the next part of the paper and will later present his analysis of findings in light of financial crises and the objectives of Shari ' ah . Findings: The Maqasid Al-Shari ' ah approach used in the analysis suggests that speculative financial instruments do not constitute a necessity, and their harmful practice must be limited to protect the religion, life, lineage, intellect and property. Originality/value: Financial speculation in general and foreign exchange in particular must be regulated. Their current practices of financial system pose significant challenges for entire economies as well as individuals. Muslims should also avoid speculative financial instruments, such as forex, because they are a clear threat to individual and state wealth and prosperity. In addition, they threaten traditional businesses and social norms in Muslim societies.